Efeitos do treinamento muscular inspiratório domiciliar sobre a atividade eletromiográfica dos músculos respiratórios em asmáticos: estudo piloto - Delgado, Renata Nóbrega (2013)
Asthma treatment aims to achieve and maintain the control of the disease for prolonged periods. Inspiratory muscle training (IMT) may be an alternative in the care of patients with asthma, and it is used as a complementary therapy to the pharmacological treatment. Thus, the aim of this study was to investigate the effects of a domiciliary program of IMT on the electromyographic activity of the respiratory muscles in adults with asthma. This is a clinical trial in which ten adults with asthma and ten healthy adults were randomized into two groups (control and training). The electrical activity of inspiratory muscles (sternocleidomastoid (ECM) and diaphragm) was obtained by a surface electromyography. Furthermore, we assessed lung function (spirometry), maximal inspiratory pressure - MIP - (manometer). The functional capacity was evaluated by six minute walk test. Participants were assessed before and after the IMT protocol of 6 weeks with POWERbreathe® device. The training and the control groups underwent IMT with 50% and 15 % of MIP, respectively. The sample data were analyzed using SPSS 20.0, attributing significance of 5 %. Were used t test, ANOVA one way and Pearson correlation. It was observed an increase in MIP, after IMT, in both training groups and in healthy sham group (P < 0.05), which was accompanied by a significant increase in ECM activity during MIP in healthy training group (1488 %) and in asthma training group (ATG) (1186.4%). The ATG also showed a significant increase in diaphragm activity in basal respiration (48.5%). Functional capacity increased significantly in the asthma sham group (26.5 m) and in the asthma training group (45.2 m). These findings suggest that IMT promoted clinical improvements in all groups, especially the ATG, which makes it an important complementary treatment for patients with asthma